Use of Social Media, Network Avenues, Blog and Scientific Information Systems Through the Website Promoting the Mediterranean Diet as a Method of a Health Safeguarding - Mariscal-Arcas, Miguel; Jimenez-Casquet, Maria Jose; Saenz de Buruaga, Borja; Delgado-Mingorance, Sonia; Blas-Diaz, Alba; Cantero, Leticia; Padial, Magdalena; Matas, Maria Eugenia; Martinez, Nuria Mohamed; Salas, Pablo; Reboredo, Alba; Lopez-Moro, Alejandro; et al. (Frontiers in Communication, 2021)
The Mediterranean Diet (MD) is considered by the Food and Agriculture Organization of the United Nations (FAO) as “the best for people and the most sustainable for the environment”. In the era of Big Data, new tools are emerging to facilitate health care research. One form of Big Data is the one that accumulates in the traffic caused by publications on the web and social networks. These data can provide valuable information about the epidemiological patterns of certain behavior and interest of the population. The objective of this study was to explore through websites and its associated official social media on information related to different publications of both international or national nutrition official agencies as well as publications of scientific diffusion for the design of future nutritional education and MD programs. This study opens up future avenues of research, such as studying the acceptance of post writing in other languages in those northern European countries where MD is being implemented. Or through the use of subtitled videos, due to the great acceptance of this format. The MD remains in 2020 considered the best option to follow a healthy diet without difficulties, therefore it is very important to continue promoting the need for good nutritional health based on its qualities.